Woolen Fabric Dyeing with Punica granatum L. Rind by Using Different Mordants - Üstün Özgür, Mahmure; Ögütgen Açikgöz, Zühal; Yilmaz Sahinbaskan, Burcu; Gümrükçü, Gülsah (Asian Journal of Chemistry, 2012)
In Turkey, there exist about 150 dye plant species that could be used in dyeing. However, these plants are not sufficiently utilized in field of cultivation. Through extension of these plants cultivation in agriculture, required raw materials in vegetable dyeing could be met. Hand woven carpets and other products dyed with dye plants are important income from domestic and foreign tourism sources. The aim of the study was to determine dyeing properties of quercetin, which is extracted from Punica granatum L. rind, using different mordants and dyeing methods on wool fabrics. The effect of mixture of the tannic acid and some selected metal salts were investigated in six difference dyeing methods by using buffer solutions at pH 4 for 1 h at 98-100 ºC with closed bath dyeing technique. The colour coordinate of dyed samples were found to lie in the yellow-brown quadrant of the colour space diagram. Colour differences in CIE L*a*b* unit, optimum mordant, dyeing methods and K/S rates of dyed wool fabrics were determined. In this study, good lightfastness (3-8), rubbing fastness (4-5) approximately and antibacterial fibers were obtained.